Moderasi Regulasi Emosi pada Pengaruh Body Image terhadap Kecemasan Sosial - 'Izzah, Nida Mukhlishotul; Nurul Lail Rosyidatul Muammaroh (Psikodinamika: Jurnal Literasi Psikologi, 2025)
Social anxiety is a natural thing and must be experienced by all individuals but differs in terms of levels. The cause of individuals feeling anxious socially is the depiction of a negative physical form or body image so that if the social anxiety felt by an individual is not immediately reduced or lowered it will have a negative impact on his interpersonal interactions. Especially in individuals who are early adults who are developmentally required to be able to interact with other individuals optimally. So what factors are needed that can reduce the tendency of social anxiety experienced by individuals. This study aims to examine whether regulating emotions can reduce the effect of body image on the tendency of social anxiety in individuals, especially in early adulthood. This research is a research with a quantitative design using accidental sampling technique that is sampling technique based on coincidence, that is, anyone who by chance meets the researcher can be used as a sample, with a total of 265 subjects. The results of the study show that emotion regulation does not act as a moderator variable on the effect of body image on social anxiety tendencies. Keywords: Anxiety; Body Image; Emotion Regulation